Sintering behaviour of forsterite bioceramics - Lee S.K.Y.; Tan C.Y.; Lai S.K.L.; Tolouei R.; Amiriyan M.; Yap B.K.; Ramesh S. (2023)
With the assistance of heat treatment, forsterite (Mg 2SiO 4) powder was successfully synthesized using talc and magnesium oxide as the basic starting materials. Sintering behavior and mechanical properties were evaluated upon sintering the synthesized forsterite compacts from 1200 C to 1500 C. Forsterite phase without any secondary phase were observed at all sintering temperatures analyzed by X-ray diffractometer (XRD). Results also showed that relative density of 90.7% was obtained at sintering temperature of 1500 C. Optimal fracture toughness (4.88 MPa.m 1/2) and Vickers micro-hardness (7.11 GPa) were achieved when sintered at 1400 C. 2011 IEEE.